2009
DOI: 10.1007/s12185-009-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of complete remission of refractory hairy cell leukemia by rituximab progressing after allogeneic hematopoietic stem cell transplantation

Abstract: The introduction of purine analogs has improved the management of hairy cell leukemia (HCL), [1] but refractory HCL remains difficult to treat. We report the case of a patient with HCL, who was refractory to purine analogs combined with rituximab, but was successfully treated by allogeneic hematopoietic stem cell transplantation (HSCT) and rituximab.A 31-year-old man was referred to our hospital in March 1999 because of bicytopenia: the white blood cell count was 1.5 9 10 9 /L, and the platelet count was 70 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…115 Regarding a case report of Zinzani et al , 116 allogeneic stem cell transplantation may be an alternative strategy in HCL patients resistant to chemoimmunotherapy. 116 Further experiences with stem cell transplantation in HCL are limited to few case reports.…”
Section: Treatment Options Results and New Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…115 Regarding a case report of Zinzani et al , 116 allogeneic stem cell transplantation may be an alternative strategy in HCL patients resistant to chemoimmunotherapy. 116 Further experiences with stem cell transplantation in HCL are limited to few case reports.…”
Section: Treatment Options Results and New Insightsmentioning
confidence: 99%
“…Kiyasu et al 115 reported on a patient suffering from HCL who was refractory to several treatment approaches inter alia to a combination therapy of cladribine and rituximab but who could be successfully treated with a combination of allogeneic hematopoietic stem cell transplantation followed by four weekly doses of 375 mg/m 2 rituximab. 115 Regarding a case report of Zinzani et al , 116 allogeneic stem cell transplantation may be an alternative strategy in HCL patients resistant to chemoimmunotherapy. 116 Further experiences with stem cell transplantation in HCL are limited to few case reports.…”
Section: Treatment Options Results and New Insightsmentioning
confidence: 99%